المعارضة السياسية في الجزائر – دراسة في الفقه الإسلامي والقانون الجزائري – - مناني, ياسين (University of Eloued جامعة الوادي, 2020)
"يتناول هذا البحث موضوع المعارضة السياسية في الجزائر – دراسة في الفقه الإسلامي والقانون الجزائري –، وقد جاءت إشكالية البحث كالآتي: إلى أي مدى استطاع المشرع الجزائري أن يؤسس لوجود معارضة سياسية بإطارها الفقهي والقانوني؟ وقد تطرق البحث إلى ثلاثة مباحث: المبحث التمهيدي: المعارضة والسلطة السياسية مدخل إلى المفاهيم المبحث الأول: المعارضة والسلطة السياسية الأسس والأحكام المبحث الثاني: المعارضة السياسية في الميزان الفقهي والقانوني-المعارضة الحزبية أنموذج- وقد توصلت الدراسة إلى مجموعة من النتائج منها: 1- تستمد المعارضة السياسية بشكل عام مشروعيتها في الفكر السياسي الإسلامي من مبدأ الأمر بالمعروف والنهي عن المنكر، المبني على أسس وقواعد صحيحة، والذي يعد أصلًا من أصول الشريعة الإسلامية. 2- اختلف أهل العلم في حكم إقامة الأحزاب السياسية على صورة كيان معارض لنظام الحكم، بين مجيز، ومانع، ومجيز بشروط."This research deals with the topic of political opposition in Algeria - a study in Islamic jurisprudence and Algerian law - and the problem of the research came as follows: To what extent was the Algerian legislator able to establish the existence of political opposition with its jurisprudential and legal framework? The research dealt with three topics: The preliminary topic: the opposition and political authority: an introduction to concepts The first topic: the opposition and political power, foundations and provisions The second topic: the political opposition in the jurisprudential and legal balance - the partisan opposition is a model - The study found a set of results, including: 1-The political opposition in general derives its legitimacy in Islamic political thought from the principle of enjoining good and forbidding vice, which is based on sound foundations and rules, and which is considered one of the origins of Islamic law. 2- Scholars differed regarding the ruling on establishing political parties in the form of an entity opposed to the regime, between permissible, prohibitive, and permissible with conditions.
مذكرة ماستر تخصص شريعة وقانون
Keywords: المعارضة السياسية- السلطة السياسية - الفقه الإسلامي - القانون الجزائري; Political opposition - political power - Islamic jurisprudence - Algerian law